Association of higher waist circumference with milder stroke severity in acute ischaemic stroke. (2nd September 2018) - Kang, Kyusik; Lee, Wong-Woo; Lee, Jung-Ju; Park, Jong-Moo; Kwon, Ohyun; Kim, Byung Kun
ABSTRACT: Objectives : Although higher body mass index (BMI) was reported to be associated with increased stroke incidence, having a higher BMI is known to be associated with better clinical outcomes after stroke. However, BMI has shown conflicting associations with baseline stroke severity. The aim of our study was to assess the relationship between waist circumference (WC) at admission and baseline stroke severity among patients with ischaemic stroke. Methods : The WC of acute stroke patients was divided into sex-specific quartiles. Baseline stroke severity was categorised as mild [National Institutes of Health Stroke Scale (NIHSS) score 0–4], moderate (NIHSS score 5–10), and severe (NIHSS score ≥11). Multinomial logistic regression was used and reference categories were men or women in the lowest sex-specific WC quartiles who had experienced a mild stroke. Results : A total of 637 female and 766 male patients were included. The adjusted OR of severe stroke were 1.3 (95% CI, 0.7–2.4) for male patients in the third WC quartile, 0.7 (95% CI, 0.3–1.5) for male patients in the second WC quartile, and 0.4 (95% CI, 0.2–0.8) for male patients in the top WC quartile. The adjusted OR of severe stroke for female patients in the third WC quartile, the second WC quartile, and the top WC quartile were 0.8 (95% CI, 0.4–1.5), 0.4 (95% CI, 0.2–0.9), and 0.7 (95% CI, 0.3–1.3), respectively. Discussion : Higher WC at admission is associated with milder baseline stroke severity among patients with acute ischaemic stroke. Abbreviations: BMI: body mass index; CE: cardioembolism; CI: confidence interval; LAA: large-artery atherosclerosis; NIHSS: National Institutes of Health Stroke Scale; OR: odds ratio; SAO: small-artery occlusion; WC: waist circumference.